2020
DOI: 10.1111/jerd.12651
|View full text |Cite
|
Sign up to set email alerts
|

Microcomputed tomography evaluation of cement film thickness of veneers and crowns made with conventional and 3D printed provisional materials

Abstract: Objective To evaluate, through microcomputed tomography (μCT), the cement film thickness of veneers and crowns made with different provisional materials. Material and Methods A veneer and a crown preparation were performed on a central incisor and a second molar of a dental model, respectively, scanned with an intraoral scanner, and the .stl files were exported to an LCD‐based SLA three‐dimensional (3D)‐Printer. Twenty‐four preparations were 3D‐printed for each veneer and crown and divided into four groups (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The authors suggested and attributed this result to the shrinkage that the material undergoes during construction and post-production. In turn, they attributed this to the manipulation of data in the STL file, where conversion and formatting were generated and could result in changes [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested and attributed this result to the shrinkage that the material undergoes during construction and post-production. In turn, they attributed this to the manipulation of data in the STL file, where conversion and formatting were generated and could result in changes [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…It is undisputed that 3D printing has a great potential for prosthetics, as doctors can prepare, scan, and print their teeth in a session in clinically relevant situations, saving time and money [78]. Using intraoral or extraoral scanners, precise virtual models of the teeth can be prepared.…”
Section: Applications In Prosthodonticsmentioning
confidence: 99%
“…A good fit is essential to guarantee the mechanical stability, durability, and health of surrounding soft tissues [78]. Insufficient adaptability can lead to dental plaque accumulation, microleaking of adhesive, discoloration of edges, and [12] Low costs [11] Complete dentures Convenient and fast [13] Accurate [14] Close adaptability [10] Removable partial denture frameworks Uniform contact pressure [15] Good mechanical properties [16] Oral and maxillofacial surgery Occlusal splints Saving time and cost [17] Surgical implants High mechanical strength [18] Adjustable porosity [19] Prostheses Convenient and fast [20] Accurate [21] Working models Improving the integrity and aesthetics [22] Reducing operative time and risk [23] Oral implantology…”
Section: Crown and Bridgementioning
confidence: 99%
“…Accordingly, these technologies can effectively save time and cost. 10 In addition, clinicians can effectively prepare optimal teeth models by using extraoral or intraoral scanners. CAD software can be used to achieve favorable restorations and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A good fit is recommended when planning for the treatment strategy to maintain the surrounding tissues' health, durability, and mechanical stability. 10 If the materials were not adequately fit, various adverse events could develop in this context. These include the development of periodontal diseases, dental caries, tooth sensitivity, lack of esthetics, discoloration, microleakage of adhesive, and dental plaque accumulation over the edges.…”
Section: Discussionmentioning
confidence: 99%